2019
DOI: 10.3390/su11113071
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farmland Abandonment in Selected Metropolitan Areas of Poland: A Spatial Analysis on the Basis of Regression Trees and Interviews with Experts

Abstract: Dynamic land use changes in metropolitan areas are global phenomena. The influence of urbanisation processes on farmland is twofold: urban encroachments predominantly take place at the expense of farmland, and also result in farmland abandonment processes, especially in Central Eastern and Southern Europe. This paper analyses determinants of farmland abandonment in 280 municipalities situated in six selected Polish metropolitan areas. The analysis, which covers secondary statistical data as well as primary dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The process of land abandonment finally results in an increased forest cover and, to a smaller extent, the conversion of arable land into built up areas. The role of factors such as farm holding size, natural conditions (soils), and migration balance in the present-day land abandonment processes in Poland's metropolitan areas was highlighted in [49]. Kolecka et al [37] indicate natural conditions (slope angle) and employment opportunities outside agriculture as the key factors determining land abandonment in the Polish Carpathians.…”
Section: Discussionmentioning
confidence: 99%
“…The process of land abandonment finally results in an increased forest cover and, to a smaller extent, the conversion of arable land into built up areas. The role of factors such as farm holding size, natural conditions (soils), and migration balance in the present-day land abandonment processes in Poland's metropolitan areas was highlighted in [49]. Kolecka et al [37] indicate natural conditions (slope angle) and employment opportunities outside agriculture as the key factors determining land abandonment in the Polish Carpathians.…”
Section: Discussionmentioning
confidence: 99%
“…The 455 sample plots surveyed in this study, each covering 1 km 2 , are mainly concentrated in the West Basin Plain (73 sample plots), Hilly Area in Basin (148 sample plots), and Basin Periphery Mountain (141 sample plots), which are the primary grain-producing areas in Sichuan Province. Of the 455 sample plots, 52 plots are located in the South West Sichuan Mountain, and 41 are located in the Western Sichuan Alpine Plateau, which has limited land resources and is sparsely populated [32]. The abandonment rates of paddy field (RPFA) and non-irrigated farmland (RNFA) have 0 and 1, suggesting that they are convergent.…”
Section: Discussionmentioning
confidence: 99%
“…Actual abandonment of farmland is defined as total cessation of cultivation in any form. Farmland is considered to be semi-abandoned when it is not used for agricultural production, but where there are certain signs of it being cultivated or managed [32]. In this paper, patches of semi-abandoned farmland were investigated; actual abandoned farmland was excluded.…”
Section: Farmland Abandonment Patches Surveymentioning
confidence: 99%
“…In recent years, with the rapid development of industrialization and urbanization, the gap between the high wages of nonagricultural employment and the low income of small-scale agricultural labor operations has become increasingly prominent, inducing a large number of ALs to shift to nonagricultural employment [37]. From the perspective of labor supply and demand, the unbalanced allocation of two factors of production, arable land and labor, can lead to the occurrence of land abandonment [38]. For example, among the ALs who abandoned land in the main grain-producing area of the Poyang Lake Plain, Li et al found that 30.93% of them indicated that the reason for their abandonment was a labor shortage [39].…”
Section: Explanation Of the Factors Affecting Arable Land Abandonmentmentioning
confidence: 99%